2021
DOI: 10.3390/ph14010047
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Body Composition on the Systemic Exposure of Paclitaxel in Esophageal Cancer Patients

Abstract: Changes in body composition are associated with chemotherapy-related toxicities and effectiveness of treatment. It is hypothesized that the pharmacokinetics (PK) of chemotherapeutics may depend on body composition. The effects of body composition on the variability of paclitaxel PK were studied in patients with esophageal cancer. Skeletal muscle index (SMI), visceral adipose tissue (VAT), and skeletal muscle density (SMD) were measured at the third lumbar vertebra on computed tomography (CT) scans performed be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“… 29 In addition, according to a pharmacokinetic study, in 184 oesophageal cancer patients treated with paclitaxel, skeletal muscle measures were not superior to BSA in predicting pharmacokinetics of paclitaxel and did not have any added value to BSA. 30 …”
Section: Discussionmentioning
confidence: 99%
“… 29 In addition, according to a pharmacokinetic study, in 184 oesophageal cancer patients treated with paclitaxel, skeletal muscle measures were not superior to BSA in predicting pharmacokinetics of paclitaxel and did not have any added value to BSA. 30 …”
Section: Discussionmentioning
confidence: 99%
“…A previous study presented that the clearance of cisplatin and paclitaxel was increased in obese patients [ 123 ]. However, underlying mechanisms for the effect of obesity on treatment outcome are currently unknown [ 123 ], and a study in patients receiving paclitaxel for esophageal cancer reported that paclitaxel dosing could not be optimized by correcting for body composition [ 124 ]. Future studies should identify if body composition measures have prognostic value for specific toxicities in patients with ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%